1978
DOI: 10.1002/j.1537-2197.1978.tb06071.x
|View full text |Cite
|
Sign up to set email alerts
|

Pollen Wall and Aperture Development in Helianthus Annuus (Compositae: Heliantheae)

Abstract: Wall development of tricolpate pollen of sunflower was studied by light and by scanning and transmission electron microscopy. The wall and colpi are initiated during the tetrad stage, producing a young, spinulate, two‐layered exine (ektexine and endexine) separated by a “spacer layer.” After release from the tetrads, the individual microspores round up and enlarge. The exine layers increase in thickness and complexity from sporopollenin contributed by the tapetum and microspores. During the mid‐vacuolate micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0
4

Year Published

1980
1980
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 48 publications
2
19
0
4
Order By: Relevance
“…It is similar to the spacer layer formed at the same stage in the microspore of ileliarirliirs (Horner & Pearson 1978). The loss of the fibrillar material later results in cavea-like spaces.…”
Section: Crr Wri-like Voidsmentioning
confidence: 52%
See 2 more Smart Citations
“…It is similar to the spacer layer formed at the same stage in the microspore of ileliarirliirs (Horner & Pearson 1978). The loss of the fibrillar material later results in cavea-like spaces.…”
Section: Crr Wri-like Voidsmentioning
confidence: 52%
“…On the other hand, the ontogeny of the tectum in Leoritodori differs from that of other genera in which the tectum is formed over the distal ends of radially oriented probacules inserted into the primexine matrix as in Sriiritpairlia (Ehrlich 1958), Silerie (HeslopHarrison 1963), I'nrliirisoriio (Larson & Lewis 1962), Iporiiueri (Godwin et al 1967) and llelicinthirs (Horner & Pearson 1978). In Leontodori the pretectal period is distinguished from that ofhtenrisin by the deposition of strongly stainable patches appearing to be detached from the plasma membrane.…”
Section: G El-ghtiz(il~mentioning
confidence: 94%
See 1 more Smart Citation
“…Regarding to the sugars, their importance was demonstrated for maturation of the epidermis, endothecium and tapetum (Clément & Audran 1995;Clément et al 1998;Castro & Clément 2007). In this subject, was also demonstrated that the middle layers also act in the access of sugars to the loculus (Clément & Audran 1995).Besides to supply the metabolic demand, sugars will compose the fibrous thickenings of the endothecium, the primexine and intine, and in some cases, also the exine (Walter & Doyle 1975;Horner & Pearson 1978). When preparing for the developmental events of pollen grains, including the pollination period, sugars can be accumulated as starch, callose, pectins, insoluble polysaccharides, disaccharides or monosaccharides (Pacini 1996;Aouali et al 2001;Clément & Pacini 2001;Pacini et al 2006).…”
mentioning
confidence: 94%
“…Besides to supply the metabolic demand, sugars will compose the fibrous thickenings of the endothecium, the primexine and intine, and in some cases, also the exine (Walter & Doyle 1975;Horner & Pearson 1978). When preparing for the developmental events of pollen grains, including the pollination period, sugars can be accumulated as starch, callose, pectins, insoluble polysaccharides, disaccharides or monosaccharides (Pacini 1996;Aouali et al 2001;Clément & Pacini 2001;Pacini et al 2006).…”
Section: Introductionmentioning
confidence: 99%